A Correlation between Digital Literacy and EFL Students' Reading Comprehension at Higher Education - Sari, Tri Ratna; Dewi Yana; Edi, Warno; Putri, Aulia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Proficient reading abilities are crucial for acquiring a language at an advanced level. Furthermore, students encounter digital information sources in the current technological era, underscoring the importance of digital abilities. Nevertheless, there is a dearth of research investigating the correlation between digital literacy and reading comprehension, particularly within the context of higher education institutions. The aim of the study is to examine whether there is a correlation between higher levels of digital literacy and reading comprehension among English as a Foreign Language (EFL) students in higher education. The research employed a correlational design. Non-probability sampling, specifically saturated sampling, was the sample technique used. The research sample consisted of twenty-five students enrolled in the fifth semester of the English Education Study Program at Universitas Riau Kepulauan. The research utilized questionnaires and test as the instruments to assess digital literacy and reading comprehension. The researcher administered the test to the sample after assessing its validity and reliability using SPSS version 23.0 for windows. The researcher employed the Pearson Product Moment to establish the relationship between digital literacy and reading comprehension. Based on data in a significance level of 5%, the analysis revealed that the r-count value (0.562) is greater than the r-table value (0.039). It approved Ha and declined Ho. The study revealed a significance correlation between students' digital literacy and reading comprehension. This research suggests integrating digital tools into learning and creating a learning environment that supports both digital skills and reading understanding simultaneously.